Wells criteria for DVT is a reliable clinical tool to assess the risk of deep venous thrombosis in trauma patients. Issue 1 (December 2016) - Modi, Shrey; Deisler, Ryan; Gozel, Karen; Reicks, Patty; Irwin, Eric; Brunsvold, Melissa; Banton, Kaysie; Beilman, Greg
Abstract Background Deep Vein Thrombosis (DVT) is a common complication in trauma patients. Venous duplex surveillance is used widely for the diagnosis of DVT, however, there is controversy concerning its appropriate use. The Wells criterion is a clinically validated scoring system in an outpatient setting, but its use in trauma patients has not been studied. This study evaluated the application of the Wells scoring system in trauma population. Methods Wells scores were calculated retrospectively for all patients who were admitted to the trauma service and underwent Venous Duplex Scanning (VDS) at the author's institution between 2012 and 2013. Correlation of Wells score with DVT and its efficacy in risk stratifying the patients after trauma was analyzed using linear correlation and receiver operating characteristic (ROC) curve. Sensitivity and specificity of Wells score in ruling out or ruling in DVT were calculated in various risk groups. Results Of 298 patients evaluated, 18 (6 %) patients were positive for DVT. A linear correlation was present between Wells score and DVT withR 2  = 0.88 (p  = 0.0016). Median Wells score of patients without DVT was 1 (1–3) compared to a median score of 2 (1–5) in those with DVT (p  < 0.0001). In low risk patients (scores <1), Wells scoring was able to rule out the possibility of DVT with a sensitivity of 100 % and NPV of 100 %, while in moderate-high risk patients (scores ≥2), it was able to predict DVT with a specificity of 90 %. Area under ROC curve was 0.859 (p  < 0.0001) demonstrating the accuracy of Wells scoring system for DVT risk stratification in post trauma patients. Conclusions A Wells score of <1 can reliably rule out the possibility of DVT in the trauma patients. Risk of developing DVT correlates linearly with Wells score, establishing it as a valid pretest tool for risk stratification.